Hopping and drift-diffusion currents in organic devices - Kanchana Sivalertporn (2018)
In physical model, the carrier transport in organic devices can be described by hopping mechanism however a number of reports were successfully applied the drift-diffusion model used normally in continuous media to numerically simulate the carrier transport in discrete organic material. In this paper the carrier transport derived from hopping and drift-diffusion models were investigated in the organic device composed of ITO/MEH-PPV/Al. The calculated current densities from both models exhibit the same feature since the boundary current at the contact were evaluated with the same current components. However the slightly differences were found in the internal electric field and carrier density. This is probably due to the slightly modification of the carrier rate equation in the nearest neighbor hopping approximation and Sharfetter-Gummel spatial discretization. © 2007 IEEE.